Laterites and Lateritic Soils: Geology, Engineering Properties and Problems - R. Shivashankar; B.C. Thomas (International Association of Lowland Technology, 2020)
Lateritic soils are abundantly available in the Konkan belt in the western coast of peninsular India, in the four southern states namely - Kerala, Karnataka, Goa and Maharashtra. Along with heavy rainfall (annual rainfall of 2000mm - 4000mm), the region is characterised by high humidity and little variation in temperatures. The typical stratification in lateritic areas consists of soft to hard lateritic crust at the top – about 3m thick, underlain by a layer of lithomargic clay (8 to 10m thick) underlain by parent rock, which is granitic gneiss. This paper briefly discusses the following aspects of lateritic soils (a) geotechnical properties, including those of laterites, lithomargic clays, lateritic lithomarges and lithomargic laterites (b) erosion studies from hole erosion tests (c) slope stability problems of excavated slopes in lateritic formations (d) role of vegetation i.e. turfing and/or trees on slopes in the stability of slopes. It is concluded that lateritic soils, especially lithomargic clays and lateritic lithomarges (1) behave somewhat like dispersive soils. (2) They are highly erosive by nature, especially lithomargic clays with higher content of sand and silt (3) Stability of both excavated and embankment slopes depends on good drainage control. Providing berms and vegetation on slopes adds to stability of slopes.